A novel plasminogen mutation in a child with hereditary periodic syndrome: A case report. Issue 4 (20th April 2022) - Akbar, Lujayn; Alazami, Anas M.; AlSaleem, Alhanouf; Alsonbul, Abdullah; Al‐Mayouf, Sulaiman M.
Abstract: Introduction: Plasminogen (PLG) deficiency is an ultrarare disease. The reported manifestations in literature were linked to pseudomembrane formation and mucosal surfaces inflammation. Recently, PLG, its activators and its receptors have gained more attention in inflammation regulatory processes, including the release of proinflammatory signaling molecules, and thus its role is believed to have clinical implications beyond what has been known. Case Report: We present a child with recurrent fever who, although managed initially as familial Mediterranean fever, later on, developed a constellation of findings that were not explained by a classified autoinflammatory disease. Genetic testing revealed a novel homozygous PLG mutation ( PLG : c.466G>A: p.D156N) and a likely benign heterozygous MEFV gene variant. We propose that the PLG mutation is responsible for the clinical manifestations, which may or may not be exacerbated by the coexistence of the MEFV variant. A relationship between the PLG pathway, inflammation, and FMF severity has been addressed recently in several studies. Conclusion: This report highlights the recently recognized role of the PLG pathway in inflammatory diseases and describes a potentially new presentation of PLG pathogenesis. Further studies are needed to confirm this finding and allow for a more definitive conclusion. Abstract : We present a child with recurrent fever. Genetic testing revealed a novel homozygous plasminogen (PLG) mutation and a likely benign heterozygous MEFV gene variant. We propose that the PLG mutation is responsible for the clinical manifestations, which may or may not be exacerbated by the coexistence of the MEFV variant. This report highlights the recently recognized role of the PLG pathway in inflammatory diseases and describes a potentially new presentation of PLG pathogenesis. Highlights: Recently, plasminogen (PLG) has gained attention in inflammatory processes regulation. This report highlights the recently recognized role of the PLG pathway in inflammatory diseases and describes a potentially new presentation of PLG pathogenesis.